C3N4/Cu/ZnFe2O4 Ternary Nanocomposites: Removal of Environmental Pollutants by the Synergy of Physical Adsorption and Photocatalysis. Issue 4 (24th January 2022) - Sun, Xiaorui; Liu, Hongfu; Yang, Jia; Fu, Mingyan; Tan, Mingdan; Yin, Guihua; Shi, Wenbing; Huang, Huisheng; Shi, Jianwei
Abstract: Although binary composites can enhance the separation efficiency of photo‐generated carriers to a certain extent, there is still space for further improvement. Here, we focus on using copper, a cheap transition metal, as an electron channel to improve the photo‐generated carrier separation efficiency of ZnFe2 O4 (ZFO) and C3 N4 (CN) composites. The kinetic constants of sample 40 %‐ZFO/CN for photodegradation reaction are 2.96 and 1.98 times than that of pure sample ZFO and CN under the same conditions. However, the kinetic constants of 3 %Cu@40 %‐ZFO/CN are 7.33 and 4.92 times than that of pure sample ZFO and CN, respectively. This is probably due to the physical adsorption performances of ternary composites for pollutants are significantly stronger than those of binary composites. The best photocatalysts achieved 90 % degradation efficiency within 15 minutes. A more reasonable photocatalytic mechanism model was proposed. Photo‐generated hole, superoxide anion, and hydroxyl radical all play an important role in the photocatalytic reaction. The importance of them is superoxide anion > photo‐generated hole > singlet oxygen > hydroxyl radical from high to low. Abstract : With the increase of ZnFe2 O4 (ZFO), the adsorption capacity of RhB on C3 N4 (CN) and ZFO binary composite increased incrementally, however, the better photocatalytic efficiency appeared on 40 %‐ZFO/CN sample. Furthermore, the 3 %Cu@40 %‐ZFO/CN ternary composite appeared the best photocatalytic efficiency, and has a dramatic improvement of adsorption efficiency. The TEM image of the ternary composite displayed there are Cu, ZFO, and CN in the 3 %Cu@40 %‐ZFO/CN sample.